An Introduction to Ancient Iranian Religion : Readings from the Avesta and the Achaemenid Inscriptions - Malandra, William W. (Book collections on Project MUSE., 1983)
When Persia fell to Islam in the mid-seventh century, the ancient Iranian religion of Zoroastrianism all but disappeared (although it is still practiced by small groups in India and Iran). As one of the dominant religions of antiquity, it influenced the.